The Integration of MAFMA and AHP Methods for Analysis and Risk Mitigation of Pasteurized Milk Production - Imam Santoso; Miftahus Sa'adah; Eva Novita Sari; Puspa Ayu Indah Prameswari; Chintya Rizki Agustina (Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
Risk and uncertainty management is an important task in industry. Risks in raw materials such as livestock products may occur from the feed. The production process is also exposed to risks, which may be caused by controllable variables. In final products, uncontrollable actions may also pose risks. This research aimed to figure out the risks and their causes in the production process of milk and to discover applicable mitigation strategies. The methods used in this study were the Multi-Attribute Failure Mode Analysis (MAFMA) method to find the causes and Analytic Hierarchy Process (AHP) to discover mitigation strategies. The results were in the form of risks in the production process caused by: 1) raw materials, 2) the production process, 3) human resources, and 4) machinery and equipment. The highest risk in the production process is posed by undetected damage to machinery and contamination during the production process. However, both are rooted in human error: poorly trained workers, omission of checking or testing, and poor supervision of the process. Mitigation strategies, i.e. standardization and supervision of the raw materials, production process, and final product, were implemented to reduce the potential risks. In the implementation of these strategies, worker participation, either as controller or as supervisor, is very important.